WORD PATTERNS OF EGYPTIAN COLLOQUIAL ARABIC (ECA) IN EGYPTIAN SPEECH EVENTS - Arief Ma'nawi; Amir Ma'ruf (Humaniora, 2015)
Morphologically, Ammya Egyptian Arabic or Egyptian Colloquial Arabic (ECA) has specific word patterns. This study is aimed at describing morphological rules of the ECA. The data were obtained through interviews using recording technique with ECA speakers in Cairo and Ismaili. They were analyzed using distributional method, a method of data analysis to connect phenomena in a given language itself. The result indicates that ECA has some word patterns which have diverse manifestations. Such diversity can be seen that V can be filled by the vowels [a], [i] and [u], C can be filled by all consonants in the ECA. In perfective verbs there are verbs patterns with singular first personal pronoun and singular masculine second personal pronoun affixes which can only be distinguished by context. A phenomenon was found that the ECA only has syllables of CV, CVC, CVVC, but not CCV, CCVC.